Analysis of VP4, VP6, and VP7 genes of G1P[8] rotavirus strains circulating in the Amazon region after rotavirus vaccine introduction - Santos, F. S (Sociedade Brasileira de Virologia, 2018)
Trabalho apresentado no Brazilian Congress of Virology, XXVI.; Mercosur Meeting of Virology, X., 2015. Florian?polis, Santa Catarina.